2011
DOI: 10.3733/ca.v065n03p141
|View full text |Cite
|
Sign up to set email alerts
|

Biofactors in food promote health by enhancing mitochondrial function

Abstract: Mitochondrial function has been linked to protection from and symptom reduction in chronic diseases such as heart disease, diabetes and metabolic syndrome. We review a number of phytochemicals and biofactors that influence mitochondrial function and oxidative metabolism. These include resveratrol found in grapes; several plant-derived flavonoids (quercetin, epicatechin, catechin and procyanidins); and two tyrosine-derived quinones, hydroxytyrosol in olive oil and pyrroloquinoline quinone, a minor but ubiquitou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Resveratrol, quercetin, procyanidins, catechins, hydroxytyrosol, and pyrroloquinoline quinine (PQQ) were found to enhance mitochondrial function [190]. Furthermore, resveratrol and quercetin (doses of ~ 500-1000 mg/day) improved the levels of anti-inflammatory mediators.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Resveratrol, quercetin, procyanidins, catechins, hydroxytyrosol, and pyrroloquinoline quinine (PQQ) were found to enhance mitochondrial function [190]. Furthermore, resveratrol and quercetin (doses of ~ 500-1000 mg/day) improved the levels of anti-inflammatory mediators.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…With respect to health effects, epidemiological studies have shown correlations between the numerous dietary intake bioactive factors and the risk of chronic diseases (Schaefer, 2006;Shenoy et al, 2011). In plants, compounds that serve as secondary metabolites have evolved to provide protective camouflage, repel predators, or facilitate electron transport and in the transformation of specific wavelengths of light into chemical energy.…”
Section: Physiologically Important Metabolites and Biofactors In Foodsmentioning
confidence: 99%
“…In plants, compounds that serve as secondary metabolites have evolved to provide protective camouflage, repel predators, or facilitate electron transport and in the transformation of specific wavelengths of light into chemical energy. Included in the discussion are descriptions for resveratrol, quercetin, various procyanidins, hydroxytyrosol, and pyrroloquinoline quinone (Schroeter et al, 2010;Shenoy et al, 2011; Figure 6). A xenobiotic is an external chemical that a given organism does not normally produce and is either eliminated or put to a novel use.…”
Section: Physiologically Important Metabolites and Biofactors In Foodsmentioning
confidence: 99%
See 2 more Smart Citations